PERTUMBUHAN DAN KELANGSUNGAN HIDUP IKAN NILA Oreochromis niloticus DALAM SISTEM RESIRKULASI - Putra, Iskandar; Setiyanto, D. Djoko; Wahyjuningrum, Dinamella (Jurnal Perikanan dan Kelautan, 2011)
Ammonia that excreted from fish metabolic activity is a serious problem inintensive aquaculture production systems because it would build-up to toxic levelin fish tanks. Therefore, recirculating system with filtration process becomes animportant component to maintain water quality in order to be an appropriatecondition for fish production. The objective of this experiment was to measuregrowth and viability fishes with three kinds of filter media, i.e., zeolith, mussel(Anodonta woodiana) as detrivorus-converter, and lettuce (Lactuca sativa) asphototrophic-converter, and one unit of the experiment as a control (without filtermedium). The result of the experiments showed fish performance of that systemsuch as survival rate, food conversion ratio, and biomass growth rate, were higherthan the others, i.e., 88 %, 1.43, and 1.18 kgs, respectively. However, fish specificgrowth rate of the treatment (3.16 %) had no significant difference (P > 0.05)compared to other treatments